Posted by **rochelle** on Sunday, January 28, 2007 at 5:45am.

Show that the equation (1) divided by (x+1) - (x)divided by (x-2)=0 has no real roots

Well, to begin, start with 1/(x+1-x). The x's cancel out because they are opposite signs, so now you have 1/1, or just 1. Then, you are dividing 1 by (x-2). In order for an expression to have roots, you have to be able to plug in the roots for x and get 0 out of the equation. In this equation, you might think that 2 is a root. However, that would make the denominator of the fraction 0, which makes the equation undefined. The only way for an equation that's a fraction to have roots is if the numerator = 0. There is no way to get that if the numerator is 1.

## Answer This Question

## Related Questions

- Estimation decimal quotient - Use compatible numbers to find the each quotient...
- Precalculus - "Show that x^6 - 7x^3 - 8 = 0 has a quadratic form. Then find the ...
- maths - simultaneous equations x + 2y = 4 3x - 4y = 7 x=3 and y = 1/2 i need to ...
- math, algebra - can someone correct this for me or help me. 6x^2y^3+ 9x^2y^3 ...
- Math - Ms. Jones wrote the equation below on the board. x divided by 42=21 If ...
- Math - Divide. Write in simplest form. 5. 1/3 divided by 2/5=5/6 6. 1/9 divided ...
- Pre Cal - Use Descartesâ€™ Rule of Signs to find the number of possible positive, ...
- Maths - q2) a) write the equation cos2x + 8cosx+9=0 in terms of cosx and show ...
- maths complex numbers - Can abs(28-7w)=7abs(w) be written as abs(w-4)=abs(w) and...
- 5th grade math - solve 1. 8/11 divided by 4 2. 3/8 divided by 3/10 3. 6 divided ...

More Related Questions